Sinergi Orang Tua Dan Pelatih Dalam Pembinaan Atlet Renang: Pendekatan Holistik (Studi Kasus Bali Pari Swimming Club) - Ni Nyoman Dewi Setiari; I Ketut Iwan Swadesi; Wasti Danardani (Jurnal Sporta Saintika, 2026)
This study departs from the view that swimming athletes’ achievement is not solely determined by physical ability and technical skill, but also by the quality of coaching that involves the active roles of parents and coaches working side by side. The purpose of this research is to analyze the role of each party and the pattern of collaboration between them in supporting athletes’ achievement at Bali Pari Swimming Club. A descriptive qualitative approach was employed, with research subjects consisting of coaches, parents, and athletes selected through a purposive sampling technique. The research instruments included an observation guide to record training situations, a semi-structured interview guide to explore participants’ experiences and perspectives, and documentation sheets to examine training programs and achievement records. Data were collected through direct observation, in-depth interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. Data validity was tested using the technique and source triangulation. The findings indicate that parents contribute through emotional support, motivation, nutritional provision, and training facilities, while coaches design and implement structured and continuous training programs to develop athletes’ technical, physical, and mental aspects. Effective communication between both parties creates a stable training environment that supports athletes’ consistency and performance.